Maido â€œUmbai Cacingâ€ Kebudayaan Jawa yang Membusuk - Riyono, Bagus; Nurhidayati, Yurisa (Faculty of Psychology, Universitas Gadjah Mada, 2011)
â€œMaidoâ€ is a peculiar term within Javanese language which meaning is so unique that itÂ has no perfect translation to Indonesian language. It has a mix meaning of denial, rejection,apathetic, or put others down. However, on the positive side, â€œmaidoâ€ could mean as anÂ attitude of critical thinking. This study aims to uncover the position of â€œmaidoâ€ withinJavanese culture, whether it is one of the local wisdom which supposed to be positive or is it aÂ â€œcultural accidentâ€ that need to be reconsidered.Â In general the purpose of this study is to understand the meaning and the origin ofÂ â€œmaidoâ€ attitude within Javanese people. By knowing that, it is expected that the academiciancould treat it proportionally as a part of the psychology of Javanese culture. The methodÂ applied to this study is phenomenology as a qualitative approach. Respondents of the studyconsist of the experts of Javanese culture and observers of the culture.Â The result shows that â€œmaidoâ€ does not have a central position in Javanese culture, andÂ the positive meaning is fading away. Currently â€œmaidoâ€ is known as a negative attitude thatis not supposed to be shown.